2014
DOI: 10.1016/j.eats.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Harvest of a Quadriceps Tendon Graft With or Without a Bone Block

Abstract: The quadriceps tendon (QT) as a graft source for anterior cruciate ligament (ACL) and posterior cruciate ligament reconstruction has recently achieved increased attention. Although many knee surgeons have been using the QT as a graft for ACL revision surgery, it has never gained universal acceptance for primary ACL reconstruction. The QT is a very versatile graft that can be harvested in different widths, thicknesses, and lengths. Conventionally, the QT graft is harvested by an open technique, requiring a 6 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 19 publications
0
68
0
Order By: Relevance
“…Using a 2–3 cm transverse incision centred over the superior pole of the patella, Fink et al have described a minimally invasive harvest technique using a double knife 8–12 mm in width (Karl Storz, Tuttlingen, Germany) and a series of specialised tendon separator and cutter (Karl Storz) to truncate the autograft proximally18 (figure 2). Slone et al have described a similar minimally invasive soft tissue-only harvest technique using a 1.5–2 cm longitudinal incision extending proximally from the superior pole of the patella, just lateral to its midpoint 19.…”
Section: New Information On Anatomymentioning
confidence: 99%
“…Using a 2–3 cm transverse incision centred over the superior pole of the patella, Fink et al have described a minimally invasive harvest technique using a double knife 8–12 mm in width (Karl Storz, Tuttlingen, Germany) and a series of specialised tendon separator and cutter (Karl Storz) to truncate the autograft proximally18 (figure 2). Slone et al have described a similar minimally invasive soft tissue-only harvest technique using a 1.5–2 cm longitudinal incision extending proximally from the superior pole of the patella, just lateral to its midpoint 19.…”
Section: New Information On Anatomymentioning
confidence: 99%
“…Thus, it is feasible to make an individual graft choice -for instance, to avoid BPTB grafts when anterior knee pain is at risk (floor tiler) or to avoid semitendinosus grafts when concomitant medial collateral ligament injury exists. Novel minimally invasive surgical harvesting techniques for quadriceps tendons promise less cosmetic burden and more clinical acceptance [77] . In a systematic review of overlapping meta-analyses, Mascarenhas et al [78] concluded that allografts were equal to autografts in terms of rerupture rates and clinical outcomes.…”
Section: Graft Choice and Graft Fixationmentioning
confidence: 99%
“…1 Among the proposed advantages are low morbidity at the harvest site [2][3][4] ; predictable size and great versatility; and the ability to harvest grafts in different widths, thicknesses, and lengths. 5 The quadriceps tendon graft can be harvested with 6,7 or without a bone block. 8 To completely avoid possible patellar fracture and reduce morbidity at the harvest site, a free bone plug graft is the solution.…”
mentioning
confidence: 99%